Implementasi Metode Pembelajaran Jigsaw Dalam Meningkatkan Motivasi Belajar Seni Budaya Peserta Didik Kelas X AK 2 SMK Negeri 2 Denpasar - I Wayan Sugama; Putu Dika Pratama; Dewa Ayu Dwita Respati (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The points of this inquire about is to extend the inspiration to memorize expressions and culture of understudies in lesson X AK 2 SMK Negeri 2 Denpasar, semester 1 scholarly year 2023/2024 with the usage of the Jigsaw learning strategy. The sort of this inquire about is Classroom Activity Investigate that was carried out in two cycles, and each cycle had four stages, to be specific, (1) arranging, (2) executing activities, (3) watching, and (4) reflecting. The investigate was carried out from October to November with understudies of lesson X AK 2 SMK Negeri 2 Denpasar as a investigate subject. In collecting information utilized perception method, appraisal of introductions, documentation, and writing. The information examination procedure approach utilized incorporates a subjective expressive investigation approach and quantitative investigation. This inquire about appears an increment within the normal esteem of expressions and culture learning results in course X AK 2 SMK Negeri 2 Denpasar from cycle I to cycle II. In cycle I appears that the students' normal esteem of expressions and culture was 77, the most noteworthy score was 90, the least score was 67, and the victory pointer was 69%. In cycle II the students' normal esteem was 87, the most elevated score was 93, the least score was 82, and the victory indicator was 100%. The increase in understudy learning results reflects the increment in students' inspiration to memorize expressions and culture.